Tingkat Pemahaman Perencanaan Karir Siswa SMA Setelah Mengikuti Layanan Klasikal Karir dengan Media Roadmap dan Pohon Karir - Nadiva Azzahra; Rahayu Ehsaniya; Alfa Kurniawati; Mufiq Zarnuji (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
This study aims to describe the level of senior high school students’ understanding of career planning after participating in classical career guidance services using career roadmap and career tree media. The study employed a descriptive quantitative approach involving 72 eleventh-grade students of SMAN 1 Salatiga. Data were collected using a career planning understanding questionnaire consisting of 14 items measured on a 4-point Likert scale and analyzed descriptively. The results showed that 91.66% of students reported clarity in their understanding of career planning, with 59.72% classified in the high category, 37.50% in the moderate category, and 6.94% in the low category. These descriptive findings indicate that the use of career roadmap and career tree media supports students in understanding career planning. Practically, the findings of this study can serve as a reference for school counselors in designing visually based classical career guidance services to support students’ career planning understanding.